Evaluasi Penyimpanan Spermatozoa Ayam Pada Suhu 5⁰C, 26⁰C Dengan Pengencer Infuse NaCl, Glukosa 5% dan 10% - Asnawi Asnawi; Maskur Maskur; Adji Santoso Dradjat (LPPM Universitas Mataram, 2021)
The purpose of this study were to compare the quality of spermatozoa stored at 26⁰C, 5⁰C using diluents of NaCl, 10% glucose and 5% glucose. The spermatozoa of a rooster was collected and divided into 6 parts, each 2 tubes diluted in a ratio of 1:1 using NaCl, Glucose5% and Glucose 10%, then each 3 tubes with different diluents were stored at 26⁰C and 5⁰C. Observations of motility, viability and abnormalities of spermatozoa were carried out half an hour, 1 hour after dilution, followed every 2 hours until the ninth hours. The results showed that spermatozoa stored for 9 hours at a temperature of 26⁰C with a physiological diluent of NaCl, 10% Glucose and 5% Glucose each were different (P, < 0.05) with motility 50 ± 0.0%, 42 ± 10.95. % and 34±8.94%, respectively. At storage temperature of 5⁰C for 9 hours, physiological NaCl, 10% glucose and 5% glucose were significantly different (P<0.05) with motility 58.00±10.95%, 46.00±8.94% and 38.00±, respectively. 10.95% in a row. The viability of spermatozoa at 26⁰C storage with 5% glucose diluent was better than 10% glucose and physiological NaCl (P<0.05), 58.93±1.27%, 42.93±1.48% and 33.43±1.27% , while the physiological NaCl diluent and 10% glucose were not significantly different (P>0.05). At 5⁰C storage the viability of spermatozoa in the three diluents was not significantly different, with values of Glucose 10%, Glucose 5% and physiological NaCl 52.57±5.15%, 52.21±5.02% and 48.14±8.09%, respectively. Spermatozoa abnormalities at storage temperature 26⁰C and 5⁰C for 9 hours using physiological NaCl diluent, 5% glucose and 10% glucose, were not significantly different and varied between 5 to 10%. Finally, it can be concluded that at room temperature storage less than 4 hours the quality of spermatozoa was better with 5% glucose diluent, while for cold storage beyond 4 hours the quality of spermatozoa with NaCl diluent was higher